Logistics for Disaster Waste Management: A Case Study of the 2019 Oil Spill in Brazil - Netto, Luiz Fernando; Sanghikian, Alex Igor [UNESP]; Yoshizaki, Hugo Tsugunobu Yoshida [UNESP]; de Brito Junior, Irineu [UNESP] (Springer Nature, 2022)
During the response and recovery phases of a disaster, an important issue is waste management, which includes generation, transportation, transfer, processing, recycling, and reuse of debris. In this paper, we analyzed the logistical process related to the management of 5400 metric tons of waste from the 2019 oil spill in Brazil, considering environmental impacts and cleaning efforts. The analyses show the quantities handled by the state governments responsible for the operation and the main destination of the residues, which was the cement industry.
Keywords: Brazilian oil spill; Disaster waste management; Logistics